Dietary tryptophan links encephalogenicity of autoreactive T cells with gut microbial ecology - Sonner, Jana K.; Keil, Melanie; Schühle, Magdalena; Deumelandt, Katrin; Röwe, Julian; Sanghvi, Khwab; Wolf, Lara; Landenberg, Anna von; Oezen, Iris; Lanz, Tobias; Mohapatra, Soumya Ranjan; Röth, Ralph; et al. (Nature Communications, 2019)
Food intake shapes intestinal microbiome composition, which in turn shapes adaptive immune responses. Here the authors show that dietary tryptophan restriction (DTR) protects mice from subsequent autoimmune neuropathology challenge by altering intestinal microbiota, highlighting the potential of diet-regulated microbiota to prevent immune pathology.